1995
DOI: 10.1182/blood.v86.7.2760.bloodjournal8672760
|View full text |Cite
|
Sign up to set email alerts
|

Desmopressin induces endothelial P-selectin expression and leukocyte rolling in postcapillary venules

Abstract: Desmopressin, (DDAVP; 1-desamino-8-D-arginine vasopressin) increases the release and activity of von Willebrand factor (vWF); however, its effects on the other major constituent of endothelial Weibel-Palade bodies, P-selectin, has not been investigated. DDAVP-induced P-selectin expression may explain DDAVP's efficacy in bleeding disorders in which vWF levels are normal. Therefore, the objective of this study is to assess the effect of DDAVP on P-selectin expression on endothelial cells of postcapillary venules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 0 publications
1
32
1
1
Order By: Relevance
“…However, this study does not contradict those results, but strengthens the rationale for our investigation. In conjunction with the results by Kanwar et al (1995), the lack of increase in cP-selectin after DDAVP infusion in our study provides evidence against intracellular storage of a soluble P-selectin in the Weibel-Palade bodies. Also, we can exclude that rapid proteolytic cleavage of membrane P-selectin expressed on the surface of endothelial cells and subsequent shedding of P-selectin occurs under physiological conditions in humans.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, this study does not contradict those results, but strengthens the rationale for our investigation. In conjunction with the results by Kanwar et al (1995), the lack of increase in cP-selectin after DDAVP infusion in our study provides evidence against intracellular storage of a soluble P-selectin in the Weibel-Palade bodies. Also, we can exclude that rapid proteolytic cleavage of membrane P-selectin expressed on the surface of endothelial cells and subsequent shedding of P-selectin occurs under physiological conditions in humans.…”
Section: Discussionsupporting
confidence: 88%
“…The main finding of our study is the lack of increase in cPselectin after DDAVP infusion, despite very recent evidence that DDAVP increases P-selectin expression on endothelial cells and increases P-selectin-dependent rolling of neutrophils on rat mesenteric venules (Kanwar et al, 1995).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…23 In vitro studies have shown improved interaction between platelets and the vascular subendothelium. 24,25 Furthermore, DDAVP has been shown to enhance Na + /Ca 2+ mobilization in platelets enhancing their ability to form procoagulant platelets and increase platelet-dependent thrombin generation. 21,23 We had one instance in which DDAVP at weight-based dose (0.3 mcg/kg) was ineffective in achieving haemostasis in a single patient with a partial test response.…”
Section: Discussionmentioning
confidence: 99%
“…Desmopressin infusion in rats causes an increase in P-selectin expression in endothelial cells [16]. It is known that P-selectin is important in promoting leucocyte adhesion to the subendothelium, which could be relevant in primary haemostasis.…”
Section: Mechanism Of Action Of Desmopressinmentioning
confidence: 99%